Caregivers burden in people in palliative care: an integrative literature review - Rezende, Gabriela; Gomes, Cristiane A.; Rugno, Fernanda C.; Carvalho, Renata C.; De Carlo, Marysia M. R. P. (Medicina (Ribeirao Preto), 2016)
Study design: Integrative literature review. Objective: To summarize the main research findings and critically analyze the evidence on the burden of caregivers of people in Palliative Care. Method: Bibliographic search in the electronic databases: MEDLINE, LILACS, CINAHL and the virtual library SciELO, with crosses between the descriptors: “Caregivers”, “Palliative Care”, “Hospice Care”, “Terminal Care” and the keywords “Burden”, “Supportive Care”. Results: 23 articles were selected, having been published in journals between January 2004 and June 2014, categorized into three units of analysis: 1. the task of caring and the consequences to the life of the caregiver (N=7); 2. the caregiver burden before the approach of death (N=8); 3. programs and support services to caregivers (N=8). The articles indicate that the caregiver burden varies according to their experience of care task and the evolution of the cared person’s illness; the caregiver needs to be received on your needs and have access to reduce the burden and improve both caregiver’s quality life as the assisted one. However, scientific evidence is considered fragile, with levels 4 (65.2%) and 5 (21.8%) and only 13% of studies present evidence considered strong. Conclusion: The issue of burden of caregivers of people in palliative care is relevant for research and for clinical practice, but there is need for studies with better methodological quality and scientific evidence to support the care for this population